2007
DOI: 10.1111/j.1365-313x.2007.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional oxidative stress responses in the Arabidopsis photorespiratory mutant cat2 demonstrate that redox state is a key modulator of daylength‐dependent gene expression, and define photoperiod as a crucial factor in the regulation of H2O2‐induced cell death

Abstract: SummaryPhotorespiration is a light-dependent source of H 2 O 2 in the peroxisomes, where concentrations of this signalling molecule are regulated by catalase. Growth of Arabidopsis knock-out mutants for CATALASE2 (cat2) in ambient air caused severely decreased rosette biomass, intracellular redox perturbation and activation of oxidative signalling pathways. These effects were absent when cat2 was grown at high CO 2 levels to inhibit photorespiration, but were re-established following a subsequent transfer to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
391
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 387 publications
(413 citation statements)
references
References 95 publications
19
391
1
2
Order By: Relevance
“…Similar features were observed in cat2 and apx1 mutants (Pnueli et al, 2003;Queval et al, 2007). It is feasible that the enhanced levels of H 2 O 2 in these plants affected the expression of transcription factors involved in the regulation of plant growth and flowering.…”
Section: Resultssupporting
confidence: 60%
“…Similar features were observed in cat2 and apx1 mutants (Pnueli et al, 2003;Queval et al, 2007). It is feasible that the enhanced levels of H 2 O 2 in these plants affected the expression of transcription factors involved in the regulation of plant growth and flowering.…”
Section: Resultssupporting
confidence: 60%
“…The evaluation of the Arabidopsis catalase2 mutants at different day lengths has revealed that photoperiod is a critical determinant of the oxidative stress response, with lesion development being enhanced in plants grown under long-day conditions (Queval et al, 2007). Singlet oxygen-induced cell death depends on the blue light/UVA-specific photoreceptor cryptochrome and differs from PCD triggered by H 2 O 2 /O 2 2 (Danon et al, 2006).…”
Section: Ros In Cell Deathmentioning
confidence: 99%
“…In recent years, the production of various transgenic Arabidopsis (Arabidopsis thaliana) plants with compromised levels of specific antioxidant enzymes and the identification of the conditional fluorescent ( flu) mutant provided important tools to assess the specific effects of O 2 2. , H 2 O 2 , and 1 O 2 within a particular subcellular compartment (Dat et al, 2003;op den Camp et al, 2003;Pnueli et al, 2003;Rizhsky et al 2003;Vandenabeele et al, 2004;Wagner et al, 2004;Queval et al, 2007). For example, with catalase-deficient [Cat(2)] plants, the signaling effects of increased photorespiratory H 2 O 2 levels could be identified (Dat et al, 2003;Vandenabeele et al, 2004;Queval et al, 2007).…”
mentioning
confidence: 99%